Proteome Analysis and Epitope Mapping in a Commercial Reduced-Gluten Wheat Product - Nye-Wood, Mitchell G.; Juhász, Angéla; Bose, Utpal; Colgrave, Michelle L. (Frontiers in Nutrition, 2021)
Gluten related disorders, such as coeliac disease, wheat allergy and baker's asthma are triggered by proteins present in food products made from wheat and related cereal species. The only treatment of these medical illnesses is a strict gluten-free diet; however, gluten-free products that are currently available in the market can have lower nutritional quality and are more expensive than traditional gluten containing cereal products. These constraints have led to the development of gluten-free or gluten-reduced ingredients. In this vein, a non-GMO wheat flour that purports to contain “65% less allergenic gluten” was recently brought to market. The present study aims to understand the alteration of the proteome profile of this wheat flour material. Liquid chromatography-mass spectrometry was used to investigate the proteome profile of the novel wheat flour, which was contrasted to a wheat flour control. Using both trypsin and chymotrypsin digests and a combined database search, 564 unique proteins were identified with 99% confidence. These proteins and the specific peptides used to identify them were mapped to the wheat genome to reveal the associated chromosomal regions in the novel wheat flour and the mixed wheat control. Of note, several ω- and γ-gliadins, and low-molecular weight glutenins mapping to the short arm of chromosome 1, as well as α-gliadins from the chromosome 6 short arm were absent or expressed at lower levels in the novel wheat variety. In contrast, the high-molecular weight glutenins and α-amylase/trypsin inhibitors were notably more abundant in this variety. A targeted quantitation experiment was developed using multiple reaction monitoring assays to quantify 359 tryptic and chymotryptic peptides from gluten and related allergenic proteins revealing a 33% decrease of gluten protein content in the novel wheat flour sample in comparison to mixed wheat control. However, additional mapping of known allergenic epitopes showed the presence of 53% higher allergenic peptides. Overall, the current study highlights the importance of proteomic analyses especially when complemented by sequence analysis and epitope mapping for monitoring immunostimulatory proteins.